A5_4 Sending an arrow to a kilometer away - Pankhania, Kishen; Keany, Connor; Newland, Rhys; Graham, Thomas; Kaiser, Felix (Physics Special Topics, 2022)
Firing an arrow as far as possible has been a topic discussed for a long time, mainly during times when single piece wooden bows were the norm, and archery was mainly a form of combat. This paper answers what peak draw weight would be required, in order to launch an arrow to a kilometer away. We found that the peak draw weight required would be 574N.